Análise imuno-histoquímica das metaloproteinases da matriz ( MMP-1,MMP-2 e MMP-9) na doença periodontal - Seabra, Flávio Roberto Guerra (2006)
The tissular destruction found in periodontal diseases is caused mainly by components of the host that have its production stimulated by the products of the microorganisms present on the plaque. Matrix Metalloproteinases (MMPs), a class of enzymes involved both in physiologic and pathologic extracellular matrix degradation are considered the main responsible for the characteristic tissular loss in periodontal disease, and the understanding of how this happens can have a series of beneficial implications for prevention, diagnosis and treatment of this illness. The aim of this work was to study the immunohistochemical expression of MMP-1, MMP-2, and MMP-9 in fragments of gingival biopsies with clinical diagnose of periodontal disease. MMP-1 has expressed significantly more than the others MMPs in gingivitis both in the epithelium (p=0,0008) and connective tissue (p=0,0049). In periodontitis, both MMP-1 and MMP-9 has expressed significantly more than MMP-2 in the epithelium (p<0,0001) and in the connective tissue (p=0,0002). MMP-1 and MMP-9 presented more expression in periodontitis than in gingivitis but MMP-1 only in the connective tissue (p=0,03) and MMP-9 in the epithelium (p=0,003) and in the connective tissue (p=0,04). In conclusion, these results indicate that the MMP-1 presents high expression in every stages of the periodontal diseases, and increases its expression in the connective tissue when the gingivitis evolves to periodontitis. Therefore, it may have an important role in connective tissue degradation and bone loss observed in disease, since early, in gingivitis, until late stages, in periodontitis, of the periodontal disease. MMP-9 has expressed more in periodontitis than in gingivitis, both in epithelium and in connective tissue. It means that this enzyme may have some importance in the progression of gingivitis to periodontitis by acting in bone resorption observed in this desease